FAKTOR-FAKTOR YANG MENYEBABKAN PERKAWINAN SIRI DI KABUPATEN KAMPAR - Anisa Bestari; Zahirman '; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated because there are many cases of marriage siri in Kampar regency. Although the religious views such marriages would be valid however, it is contrary to marriage laws regarding registration of marriages. Besides, it also usually such marriages would harm women. Therefore the formulation of the problem of this study is what factors lead to marriage siri in Kampar regency. The purpose of this study was to determine what factors are causing the marriage siri in Kampar regency. This research is useful for the reader to add insight and information about the marriage siri.This research method is a combination that is the incorporation of qualitative and quantitative. Data collection instruments used were a questionnaire consisting of 15 questions and 17 questions interview questionnaire distributed to 68 respondents. Data collection through questionnaires, interviews, documentation, and literature. The results of this study are a major cause of Kampar regency society meakukan siri marriage is due to psychological factors with a percentage of 100% and legal factors with the percentage of 24.99%, the cost factor of 13.6%, 13.23% biological factors, social factors 12.25%, and the factor of school / workplace 3.67% Keywords: Marriage Siri